Correlations between soil characteristics and radioactivity content of Vojvodina soil. (January 2017) - Forkapic, S.; Vasin, J.; Bikit, I.; Mrdja, D.; Bikit, K.; Milić, S.
Abstract: During the years 2001 and 2010, the content of 238 U, 226 Ra, 232 Th, 40 K and 137 Cs in agricultural soil and soil geochemical characteristics were measured on 50 locations in Northern Province of Serbia – Vojvodina. The locations for sampling were selected so that they proportionately represent all geomorphologic units in the region. The content of clay and humus varied within wide limits depending on soil type and influence the activity concentrations of radionuclides. In this paper we analyzed correlations between radionuclides content and geochemical characteristics of the soil. Possible influence of fertilizers on 238 U content in soil was discussed. The main conclusion is that measured maximal activity concentrations for 238 U (87 Bq/kg), 226 Ra (44.7 Bq/kg), 232 Th (55.5 Bq/kg) and 137 Cs (29 Bq/kg) at 30 cm depth could not endanger the safety of food production. The process of genesis of soil and cultivation mode plays a dominant role on the characteristics of the soil. The most significant correlation was found between the activity concentrations of 40 K and clay content in agricultural soil. Highlights: Radioactivity content and chemical characteristics of soil samples were correlated. Comparison of radionuclide concentrations in soil (in 2001 and 2010) was performed. Possible influence of fertilizers on 238 U content in soil was discussed. Maximal dry weight concentrations of radionuclides in plants were calculated.